Facing the Industrial Revolution 4.0 Era Through 360-Degree Leadership Education for Accounting Students - Hanny Hanny; Nunik Lestari Dewi; Sinta Setiana; Meliana Halim (Jurnal Akuntansi, 2023)
The era of the Industrial Revolution 4.0 causes new challenges that require accountants to develop their skills continuously, including leadership skills (Biro Kerjasama dan Komunikasi Publik Kemenristekdikti, 2018). In connection with the development of leadership skills in the accounting profession, this research aims to examine the influence of 360-degree-based Leadership Education on accounting students' perceptions of the ideal leadership concept and its characteristics. This research also examines the differences in perceptions of accounting students regarding leadership and leadership characteristics before and after receiving their leadership education program. The unit of analysis for this research is accounting students who have taken 360-degree based leadership education and were students who have been researched respondents in the previous year when they had not taken this. This research used the Purposive Sampling method with a sample size of 92 people. The research hypothesis was tested by The Comparative Test and the Simple Linear Regression method. The results of this study indicate that 360-Degree Based Leadership Education influences students' perceptions of leadership and its ideal characteristics. This study also indicates that students' perceptionsregarding the concept and characteristics of ideal leadership have been changed after participated in this Leadership Education. Keywords: The 360-Degree Based Leadership Education, Leadership, Perception, Leadership Characteristics, and Student of Accounting Program